A produção do espaço urbano e os planos diretores de Uberlândia (MG): um estudo do bairro Fundinho na ótica do planejamento estratégico - Justino, Alessiane Silva (2016)
This research analysed the (re)production and transformation of space and urban landscape in Fundinho district of Uberlândia. This work observed the contributions of the master plan of 2006 in the current socio-spatial configuration of the neighborhood. To get the expected result, the methodology was based on the principles of strategic planning, with the presentation of a diagnosis, the development of a SWOT matrix and propose two scenarios: the inertial space and the desired space. It was done a bibliographic reference on the production of urban space and its relationship with the city and memory. It was also described the proposed urban intervention according to the concepts of Vargas and Castilho authors. Then they were exposed two examples of cities that use in their urban interventions the methodology of Strategic Planning: Barcelona, a world reference, and the Brazilian case of the Porto Maravilha, in Rio de Janeiro. After the development of bibliographic references, a characterization of Fundinho was carried out, with eyes on the Urban Planning. At first, the historical characterization of the appearance of the neighborhood was carried out and then the transformations in space and landscape from the implementation of guidelines stemming the urban plans of 1908 and 1954 and the master plans of 1994 and 2006. As 2006 plan unfolding, the proposals of the redevelopment project of central area and the Fundinho neighborhood were presented. From the analyzes of the plans, it was realized that few guidelines were implemented for Fundinho. The ones that really contributed were the consolidation of the district as the Cultural Zone Fundinho and the prohibition of its vertical integration. Considering the results obtained from the analysis of the plan's guidelines director of 2006, which were not consolidated for the most part, the chapter three sought from strategic planning to propose a desired setting for the neighborhood. At first, the strengths/weaknesses and opportunities/threats of five elements of urban morphology were identified (open spaces, street furniture, building, urban mobility, stroke). So that then the SWOT matrix was developed, that guided along the interviews with the various actors of the neighborhood, the proposition of the desired scene, seeking above all to give priority to pedestrian movements and integration and optimization of various cultural buildings and open spaces (squares) that make up the Fundinho.